2020
DOI: 10.3390/ijerph17176201
|View full text |Cite
|
Sign up to set email alerts
|

Self-Determination in People with Intellectual Disability: The Mediating Role of Opportunities

Abstract: The Convention on the Rights of Persons with Disabilities have proclaimed the basic right of people to make one’s own choices, have an effective participation and inclusion. Research in the field of disability have stressed self-determination as a key construct because of its impact on their quality of life and the achievement of desired educational and adulthood related outcomes. Self-determination development must be promoted through specific strategies and especially, by providing tailored opportunities to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Based on these premises, the current literature highlights the need to further study the self‐determination skills of this group and the variables that can affect it. In particular, they suggest further research on elements that influence the development of self‐determination, such as age (Kåhlin et al, 2016; Wehmeyer, 2020), place of residence (Kåhlin et al, 2016; Sexton et al, 2016), characteristics of support received (Vicente et al, 2020), mental health issues (Behzadnia et al, 2020; Tang et al, 2020) and gender (McCausland et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these premises, the current literature highlights the need to further study the self‐determination skills of this group and the variables that can affect it. In particular, they suggest further research on elements that influence the development of self‐determination, such as age (Kåhlin et al, 2016; Wehmeyer, 2020), place of residence (Kåhlin et al, 2016; Sexton et al, 2016), characteristics of support received (Vicente et al, 2020), mental health issues (Behzadnia et al, 2020; Tang et al, 2020) and gender (McCausland et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A lack of autonomy leads to a lower level of production and motivation [8]. Regarding the applied level, self-determination skills are important for students with learning disabilities (LD) at all stages of education and beyond [9].…”
Section: Self-determination Theory (Sdt)mentioning
confidence: 99%
“…The literature indicates that students with mild mental disabilities possess a moderate level of selfdetermination skills but then show remarkable improvement after the implementation of a training program that links their experiences with reality in the development of the skills of making choices and decision-making [9,13]. The level of psychological empowerment, self-regulation, and self-realization among students with mental disabilities varies on the scale of self-determination skills in accordance with the opportunities available in the community and at home.…”
Section: Skills Of Students With Disabilitiesmentioning
confidence: 99%
“…In a cross-context comparison, Spanish youths with ID enjoyed more self-determination opportunities at school than at home [16] and many of their parents had little knowledge of self-determination and exhibited an over-protective manner towards their children [17]. A recent study also observed a mediating role of environmental opportunities in the relationship between self-determination and ID level [18].…”
Section: Introductionmentioning
confidence: 99%